2021
DOI: 10.14814/phy2.15040
|View full text |Cite
|
Sign up to set email alerts
|

Transfer‐function‐free technique for the noninvasive determination of the human arterial pressure waveform

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Although this phase of the cardiac cycle spanned between DBP and ∼65% of the PP, our results indicated that, on average, P c was determined for its 91.5% by DBP and only for its 8.5% by SBP (Figure 4). We obtained similar results when estimating cPWV via the lnDUloop method, a linear regression between blood velocity (U) and the natural logarithm of the diameter distension (lnD) in early systole (Giudici et al, 2021d). These findings suggest that, as regional PWV, loop methods provide nearly diastolic measures of PWV and that DBP should be regarded as the main driver of their BP-dependency.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Although this phase of the cardiac cycle spanned between DBP and ∼65% of the PP, our results indicated that, on average, P c was determined for its 91.5% by DBP and only for its 8.5% by SBP (Figure 4). We obtained similar results when estimating cPWV via the lnDUloop method, a linear regression between blood velocity (U) and the natural logarithm of the diameter distension (lnD) in early systole (Giudici et al, 2021d). These findings suggest that, as regional PWV, loop methods provide nearly diastolic measures of PWV and that DBP should be regarded as the main driver of their BP-dependency.…”
Section: Discussionsupporting
confidence: 55%
“…2 and rearranging using Eq. 1 leads to the following relationship between PWV and γ 0 , as previously demonstrated (Giudici et al, 2021d) (refer to Eqs A1-A7 in Appendix for the detailed calculations):…”
Section: Theoretical Backgroundmentioning
confidence: 63%
“…In summary, until the vagaries of estimating central BP based on inevitable current brachial BP calibration are eliminated -and these methods are emerging [2,3] to this commentator, central BP offers little of value over the hugely 'validated' brachial BP. Using arterial function measured as aortic pulse wave velocity is quite another and more valuable a matter -not available in UK Biobank.…”
mentioning
confidence: 99%